CHOROIDEREMIA: Retinal Degeneration With an Unmet Need. Issue 11 (November 2019) - Pennesi, Mark E.; Birch, David G.; Duncan, Jacque L.; Bennett, Jean; Girach, Aniz
Abstract : Purpose: Choroideremia is an incurable, X-linked, recessive retinal dystrophy caused by loss of function mutations in the CHM gene. It is estimated to affect approximately 1 in 50, 000 male patients. It is characterized by progressive degeneration of the retinal pigment epithelium, choroid, and photoreceptors, resulting in visual impairment and blindness. There is an unmet need in choroideremia, because currently, there are no approved treatments available for patients with the disease. Methods: We review the patient journey, societal impact, and emerging treatments for patients with choroideremia. Results: Its relative rarity and similarities with other retinal diseases in early years mean that diagnosis of choroideremia can often be delayed. Furthermore, its impact on affected individuals, and wider society, is also likely underestimated. AAV2-mediated gene therapy is an investigational treatment that aims to replace the faulty CHM gene. Early-phase studies reported potentially important visual acuity gains and maintenance of vision in some patients, and a large Phase 3 program is now underway. Conclusion: Choroideremia is a disease with a significant unmet need. Interventions that can treat progression of the disease and improve visual and functional outcomes have the potential to reduce health care costs and enhance patient quality of life. Abstract : Choroideremia is an incurable, X-linked, recessive retinal dystrophy resulting from mutations in the CHM gene, which encodes for REP1. It is characterized by progressive degeneration of the retinal pigment epithelium, choroid, and photoreceptors resulting in visual impairment and blindness. The authors review the patient journey, societal impact, and emerging treatment strategies.